Risk Factors for Acute Kidney Injury in Children: A Literature Review - Wea, Lidwina Dewiyanti (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
The incidence of acute kidney injury (AKI) in children has shown a recent increase. Several contributing factors include the emergence of new diseases such as COVID-19 and the use of nephrotoxic drugs. This literature review aims to identify the risk factors associated with AKI in pediatric populations. The method used was a literature review conducted across three databases: ScienceDirect, PubMed, and Google Scholar, using the search keywords "children," "acute kidney injury," and "risk factors." A total of 10 primary articles were selected for review. The findings indicate that risk factors for AKI in children include comorbidities such as diabetes mellitus with diabetic ketoacidosis, COVID-19, acute gastroenteritis, malaria, post-cardiac surgery, liver transplantation, wasp stings, critical illnesses requiring intensive care, the use of nephrotoxic substances such as ethylene glycol and diethylene glycol, and blood transfusions. The increasing prevalence of these risk factors has significant implications for nursing care. Nurses are expected to enhance their understanding of AKI to improve management strategies and reduce morbidity and mortality related to acute kidney injury in children.